Perspectives of higher education during the SAR COV 19 pandemic: a challenge for change (Revista Electrónica Calidad en la Educación Superior, 2023)
In the face of the pandemic produced by COVID-19, the University of El Salvador forced to adapt teaching, research, and social projection, using computer technology. Teachers assumed a transition to modify the classes and, make the adjustments that must be achieved from the planning, design, and preparation of the program and evaluations. The objective of the study was to establish the perception of teachers about the transition from face-to-face education to virtual education. The methodology used the qualitative approach, the participant observation tools, and the semi-structured interview was used. The results evidenced the search for interactive content and virtual assessment alternatives as the main perception. The development of content, evaluations and improvement of teaching practices from the different virtual environments established.
Keywords: Virtual Education; Methodology; Virtual environment; Online teaching-learning